El otro “colaborador”: una mirada comparada sobre los facilitadores de los cárteles en el derecho de la competencia - Calderón López, Andrés (2018)
The facilitators or informers have become important subjects in the field of Competition Law. However, just as they have served to fight against the cartels, they have also been used by the latter to facilitate and cover up their organization and activities.In the present article, the author seeks to explain and analyze the first cases resolved by the national competition authority in which said facilitators have been immersed. Likewise, an analysis of the jurisprudence on the subject is made in the United States, the United Kingdom and the European Union. Finally, the national legislation and jurisprudence on the subject is analyzed in the light of comparative law.